Effect of nitrogen concentration on nano-structure and high-temperature strength of 9Cr-ODS steel. (August 2018) - Oka, Hiroshi; Tanno, Takashi; Ohtsuka, Satoshi; Yano, Yasuhide; Kaito, Takeji
Highlights: Microstructure and mechanical properties of 9Cr-ODS steel were investigated as a function of nitrogen concentration. hardness and tensile strength were degraded as nitrogen concentration increased, due to the decreased amount of residual α-ferrite phase. Formation of coarse YTi precipitates was observed, suggesting degradation of the nano-particle distribution. Nitrogen concentration specification for 9Cr-ODS steel should be stricter than the current level. Abstract: The objective of this study was to investigate the effect of nitrogen concentration on mechanical properties and nano-structure of 9Cr oxide dispersion strengthened (ODS) ferritic/martensitic steel. 9Cr-ODS specimens with the wide range of nitrogen concentration, from 0.004 to 0.110 wt%, were systematically investigated by hardness and tensile tests and several microstructural characterization methods. Hardness and tensile strength at 973 K were significantly decreased as nitrogen concentration increased, due to the decrease in the amount of the residual α-ferrite phase. Coarse inclusions containing Y and Ti, which could negatively affect creep strength and processability, were formed, and that suggested degradation of the nano-particle distribution. The technical knowledge obtained in this study will contribute towards the setting of a reasonable nitrogen concentration specification for 9Cr-ODS steel.